2017
DOI: 10.1016/j.bpj.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptors Contain Two Conserved Packing Clusters

Abstract: G protein-coupled receptors (GPCRs) have evolved a seven-transmembrane helix framework that is responsive to a wide range of extracellular signals. An analysis of the interior packing of family A GPCR crystal structures reveals two clusters of highly packed residues that facilitate tight transmembrane helix association. These clusters are centered on amino acid positions 2.47 and 4.53, which are highly conserved as alanine and serine, respectively. Ala2.47 mediates the interaction between helices H1 and H2, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…In nonolfactory class A GPCRs, position 4.53 is conserved as S39%, A33%, V8%, T4%, C3.5%, P3%, G3%, I2%, and M1.5%, and position 5.47 is conserved as F65%, Y11%, L10%, N3.5%, V3%, G2%, I2%, and C2%. Position 4.53, as well as position 2.47, has been identified as a conserved packing cluster center in class A GPCRs, and its mutation in leucine (A 4.53 L) in Rhodopsin disrupts the structure of the receptor (42). In the β2-adrenergic receptor, S 4.53 belong to the motif S 4.53 xxxS 4.57 which does not participate to the functionality of the receptor and seems to be more involved in helix packing, maintaining the stability of the receptor (43).…”
Section: Discussionmentioning
confidence: 99%
“…In nonolfactory class A GPCRs, position 4.53 is conserved as S39%, A33%, V8%, T4%, C3.5%, P3%, G3%, I2%, and M1.5%, and position 5.47 is conserved as F65%, Y11%, L10%, N3.5%, V3%, G2%, I2%, and C2%. Position 4.53, as well as position 2.47, has been identified as a conserved packing cluster center in class A GPCRs, and its mutation in leucine (A 4.53 L) in Rhodopsin disrupts the structure of the receptor (42). In the β2-adrenergic receptor, S 4.53 belong to the motif S 4.53 xxxS 4.57 which does not participate to the functionality of the receptor and seems to be more involved in helix packing, maintaining the stability of the receptor (43).…”
Section: Discussionmentioning
confidence: 99%
“…H211P) or introduce bulky side chains into regions of tight helix packing. Crystal structures reveal the 7TM bundle of rhodopsin contains both tightly packed and more loosely packed helices (Sanchez-Reyes et al, 2017). Two separate interior packing clusters (1&2) were identified that mediate interactions between TM helices H1 and H2 or H3 and H4 respectively.…”
Section: Structural and Biochemical Basis Of Rhodopsin Rp Mutantsmentioning
confidence: 99%
“…These packing clusters are conserved in GPCRs and are composed of amino acids with small side chains. The residue A164 is a component of packing cluster 2 and presumably its mutation to a more bulky valine (A164V) could disturb rhodopsin folding and stability by disrupting formation of this packing core leading to misfolding (Sanchez-Reyes et al, 2017; Stojanovic et al, 2003).…”
Section: Structural and Biochemical Basis Of Rhodopsin Rp Mutantsmentioning
confidence: 99%
“…In non-olfactory class A GPCRs, position 4.53 is conserved as S39%, A33%, V8%, T4%, C3.5%, P3%, G3%, I2%, M1.5% and position 5.47 is conserved as F65%, Y11%, L10%, N3.5%, V3%, G2%, I2%, C2%. Position 4.53, as well as position 2.47, has been identified as a conserved packing cluster center in class A GPCRs and its mutation in leucine (A 4.53 L) in Rhodopsin disrupts the structure of the receptor (41). In the β2-adrenergic receptor, S 4.53 belong to the motif S 4.53 xxxS 4.57 which doesn't participate to the functionality of the receptor and seems to be more involved in helix packing, maintaining the stability of the receptor (42).…”
Section: Discussionmentioning
confidence: 99%